Wherever you go - Peterson, Tracie (Peterson, Tracie. Brookstone brides, 2019)
In 1901, Mary, an accomplished sharpshooter, can't rest until the man who killed her brother is brought to justice. Journalist Christopher is immediately captivated by Mary--but getting close to someone would threaten to bring his past to light. Can they find healing from the past together?